Disability and social protection in Asia - Rogers, Joanna; Asian Development Bank (S.I. Asian Development Bank, 2021)
Persons with disabilities are among the poorest and most vulnerable segments of society and comprise a growing proportion of Asia's population. Despite an increase in overall expenditure on disability-targeted programs during the past decade, governments in the region are generally poorly prepared to provide the level of support needed. This brief discusses what disability inclusive social protection means and looks at progress, barriers, and opportunities for the region.
Keywords: People with disabilities -- Asia; Human services -- Asia